Marburgvirus: A Global Virus, not just an African problem - Robinson, Jared; Banerjee, Indrajit; Leclézio, Alexandra (Journal of Advances in Internal Medicine, 2023)
The Marburg virus (MBV) phylogenetically belongs to the filovirus family and its clinical picture, spread and virulence resemble the Ebola virus very closely. The marked virulence of MBV is of great concern for not only the African region, but the globe in its entirety as a recent outbreak of the virus from a lab handling African green monkeys has rapidly spread to Uganda, South Africa, Kenya and Angola. On contamination of the virus the individual develops a plethora of symptoms with haemorrhage, seizures and shock being the most profound and deadly. No drug nor vaccine or cure is available against the deadly progression and course of the virus, and thus it often disseminates through households, between close loved ones and ultimately leaving a trail of death in its wake. It is now of upmost importance that international funding, knowledge and expertise become unified for the greater good; to develop treatments and vaccines to such viruses a likened to Ebola and Marburg virus to not only protect oneself, but humanity across all boarders around the world.